1997
DOI: 10.1086/514098
|View full text |Cite
|
Sign up to set email alerts
|

Antileukoprotease: An Endogenous Protein in the Innate Mucosal Defense against Fungi

Abstract: Previous studies have suggested that endogenous protease inhibitors may participate in the mucosal host defense. Antileukoprotease (ALP) is an important protease inhibitor found on various mucosal surfaces, including those of the respiratory and genital tracts. This study reports on the antimicrobial activity of recombinant (r) ALP toward the human fungal pathogens Aspergillus fumigatus and Candida albicans. rALP expressed pronounced fungicidal activity toward metabolically active A. fumigatus conidia and C. a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(48 citation statements)
references
References 43 publications
1
47
0
Order By: Relevance
“…One recent study reported that the SLPI (a member of the chelonianin family) has well-characterized fungicidal and antibacterial activities [43]. But the molecular mechanisms of SLPI responsible for its antibacterial activities are still unclear, but they parallel other AMPs in their cationic ionic ability to destabilize anionic cell membranes of bacteria [44].…”
Section: Discussionmentioning
confidence: 99%
“…One recent study reported that the SLPI (a member of the chelonianin family) has well-characterized fungicidal and antibacterial activities [43]. But the molecular mechanisms of SLPI responsible for its antibacterial activities are still unclear, but they parallel other AMPs in their cationic ionic ability to destabilize anionic cell membranes of bacteria [44].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we observed that CHI3L1 alone was sufficient to induce the expressions of mouse ␤-defensin-3, CRAMP, and SLPI, all of which have well-characterized fungicidal activities (42,43). CHI3L1 has also been shown to possess pro-and anti-inflammatory properties (35,36,40) and to induce the expression of proinflammatory cytokines, such as IL-1␤ (34).…”
Section: Figmentioning
confidence: 99%
“…In monocytes, SLPI is capable of entering the cell and localising to both the cytoplasm and nucleus (Taggart et al 2005) and can inhibit degradation of key proteins that activate NF-jB Taggart et al 2002) or can prevent NF-jB binding to promoter regions of inflammatory genes (Taggart et al 2005). Additionally, SLPI possesses key anti-microbial capabilities including activity against both bacteria and fungi (Tomee et al 1997;Wiedow et al 1998) and illustrates anti-viral properties against HIV (Ma et al 2004;McNeely et al 1997). Despite the potential advantages, treatment with aerosolized SLPI has proved unimpressive (Vogelmeier et al 1990).…”
Section: Impact Of Cf Therapies On Neutrophil Function and Inflammationmentioning
confidence: 99%